Römerzeitliche Pflanzenreste aus Porcuna, Prov. Jaén, in Andalusien - Stika, Hans-Peter; Berihuete Azorín, Marian; Heiss, Andreas; Voropaeva, Inga (Madrider Mitteilungen, 2020)
The 18 samples from Porcuna, covering Ibero-Roman (2nd/1st c. BC) until Flavian times (end of the 1st c. AD), though resulting in 19.086 plant remains, display only a subset of the domesticated and useful plants which are to be expected for this time and period. Four cereal species were found, namely oats (Avena cf. sativa), barley (Hordeum vulgare), bread wheat (Triticum aestivum), and emmer (T. dicoccum). The identified pulses were chickpea (Cicer arietinum), lentil (Lens culinaris), grasspea (Lathyrus sativus/cicera), pea (Pisum sativum), and broad bean (Vicia faba). Flax (Linum usitatissimum) was also found. However, the whole find assemblage was largely dominated by remains of olive (Olea europaea), fig (Ficus carica), and grapevine (Vitis vinifera). The numerous residues of olive oil production discovered in the site of San Benito were most probably used as fuel in the town of Obulco. In spite of the still difficult state and ambiguous results from the research into general olive domestication it can safely be assumed that this tree was already cultivated in the region in pre-Roman times. Since the Roman period latest, olive cultivation and oil pressing has been an inherent part of Andalusian agriculture.